2018
DOI: 10.3389/fmicb.2018.01984
|View full text |Cite
|
Sign up to set email alerts
|

Lactic Acid Bacterium Population Dynamics in Artisan Sourdoughs Over One Year of Daily Propagations Is Mainly Driven by Flour Microbiota and Nutrients

Abstract: This study aimed to: (i) assess at what extent traditional, daily propagated, sourdough can be considered a stable microbial ecosystem; (ii) ascertain the drivers of stability/variability. For this purpose, samples of sourdough, flour and environment were collected over 1 year from three different bakeries located in Altamura, Castellana Grotte, and Matera. Culture-dependent and –independent analyses were carried out on all the samples. In addition, sourdough and flour were subjected to biochemical characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 55 publications
0
15
2
Order By: Relevance
“…As in wild grasslands, a mature starter’s final ecology hinders colonization by new species (introduced during refreshments) in ways that are not yet clear, but closely connected to organic acid production and other competitive behaviors. While some researchers have explored microbial succession in starters over time ( Minervini et al, 2018 ), we do not conclusively know how the long-term age of a starter affects its microbial community and functional characteristics. Exploring the relationship between a starter’s age and its microbial ecology, resiliency to land management changes, and sensory quality may be an interesting direction for future research.…”
Section: Microbial Ecologymentioning
confidence: 97%
See 2 more Smart Citations
“…As in wild grasslands, a mature starter’s final ecology hinders colonization by new species (introduced during refreshments) in ways that are not yet clear, but closely connected to organic acid production and other competitive behaviors. While some researchers have explored microbial succession in starters over time ( Minervini et al, 2018 ), we do not conclusively know how the long-term age of a starter affects its microbial community and functional characteristics. Exploring the relationship between a starter’s age and its microbial ecology, resiliency to land management changes, and sensory quality may be an interesting direction for future research.…”
Section: Microbial Ecologymentioning
confidence: 97%
“…Flour helps to introduce microorganisms into the sourdough medium ( Reese et al, 2020 ). Flour also supplies different nutrients (i.e., carbohydrates and amino acids) and non-nutrients (i.e., phenolic acids, amylase, ash), the presence and concentrations of which can influence bacteria and yeast species survival ( Vogelmann & Hertel, 2011 ; Minervini et al, 2014 ; Minervini et al, 2018 ; Gänzle, 2014 ). For example, different bacteria and yeast preferentially digest different saccharides, which can influence species co-occurrence through either mutualism or antagonism ( Gracia-Lázaro et al, 2018 ).…”
Section: Sourdough Starter Maintenance As “Land Management”mentioning
confidence: 99%
See 1 more Smart Citation
“…Backslopped spontaneous sourdough productions starting from scratch go through a three-step fermentation cascade with respect to the growth of the bacterial communities in the flour-water mixture, in particular LAB ; Van der Meulen et al 2007;De Vuyst et al 2009Ercolini et al 2013;Minervini et al 2014;De Vuyst, Van Kerrebroeck, and Leroy 2017;Oshiro, Zendo, and Nakayama 2021). The microbial load of the flour [< 4 to 7 log (CFU/g)] and its nutrient availability, as well as the physicochemical parameters of the flour-water mixture, such as temperature, DY, pH, total titratable acidity and oxygen tension, and the fermentation time, determine the start and course of the microbiology of a backslopping process for sourdough production (Corsetti 2013;De Vuyst, Van Kerrebroeck, and Leroy 2017;Minervini et al 2018;Oshiro et al 2020). Hence, fermentation of the flour-water mixture starts with autochthonous, sourdough nonspecific bacteria, such as proteobacteria, staphylococci and diverse LAB species, belonging to the enterococci, lactococci, and streptococci.…”
Section: Flour Fermentation For Sourdough Productionmentioning
confidence: 99%
“…They had also been mentioned in studies describing flour microbiota, and the results were in accordance with those of De Angelis et al ( 2019) who compared the microbiotas of soft and durum wheat flour using culture independent methods. Minervini et al (2018a) analyzed the microbiotas of three different flours, and found the species F. sanfranciscensis in every sample (4% of all the strains isolated from the flour). This was higher than what we found, and could have been related to bias affecting the culture independent analyses, where rare species can go undetected.…”
Section: Flour-associated Species Were Mainly Plant-associated Microorganismsmentioning
confidence: 99%